A silicon-based compact triplexer using Bragg grating assisted non-reciprocal single microring resonator. (April 2020) - Chen, Jingyuan; Gao, Di
Highlights: A triplexer using active magneto optical garnet is proposed for the first time. Non-reciprocal rings assisted by gratings make the novel triplexers ultra-compact. The integrated metallic micro strips result in a flexibly configurable triplexer. The device with fair simulation results boosts network capacity more efficiently. Scheme's principle is adaptable since Mach-Zehnder structure can also be used. Abstract: An ultra-compact silicon triplexer based on waveguide Bragg grating assisted non-reciprocal optical ring add-drop filter has been proposed. This novel scheme consists of two straight strip waveguides laterally coupled to a microring resonator. A magneto-optically active material deposited inside the microcavity is etched to induce strong non-reciprocity, which can cause resonance wavelength splitting ΔλMO of two counter propagating modes. Uniform Bragg grating reflector is fabricated in proximity to one of the input/output (I/O) ports. As a result, two downstream WDM channels (1490 nm/1550 nm) can be separated into the output ports of strip waveguide below the ring resonator, while the third channel considered as upstream signal is transmitted through the waveguide above the microring without any interaction with either the microring resonator or the waveguide Bragg grating reflector. Results show that a total length of 13.5 μm with the highest isolation ratio (IR) of 35 dB is obtained at the adjacent ports of the same strip waveguide; the lowest crosstalk (XT) of −38 dB for 1310 nm channel has also been obtained.